Food Safety Issues in International Trade - Ronald H. Schmidt; Robert P. Bates; Douglas L. Archer; Keith R. Schneider (EDIS, 2004)
With the formation of the World Trade Organization (WTO) in 1995, specific principles and rules were conceived. These rules, or Sanitary & Phytosanitary Measures (e.g., SPS Agreement), relate to three primary issues or concerns: food safety, animal health, and plant health. While still controversial, the WTO/SPS Agreement does provide for more detailed control of food safety concerns and for more standardization and harmonization regarding rules and regulations. This document is FSHN034, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: March 2003.